Insights from the “Red Devil” AT 2022fpx: A Dust-reddened Family of Tidal Disruption Events Excluded by Their Apparent Red Color? - Zheyu Lin; Ning Jiang; Yibo Wang; Xu Kong; Shifeng Huang; Zesen Lin; Chen Qin; Tianyu Xia (The Astrophysical Journal)
We report unnoticed but intriguing features in the peculiar nuclear transient AT 2022fpx, and investigate its type. These features include the constantly red optical color of g − r > 0, a stable soft X-ray flare ( kT ∼ 100 eV) in the past ∼550 days, a prominent mid-infrared echo peaked at ∼10 ^43.3 erg s ^−1 , and the confirmation of a weak active galactic nucleus by weak flares in pre-event Wide-field Infrared Survey Explorer mid-infrared light curves with no contemporary optical, radio or X-ray counterparts. The combination of the optical red color and possible origin of a tidal disruption event (TDE) in AT 2022fpx is particularly attractive, as it challenges the most widely accepted and adopted “blue color” criterion for optical TDE selection. Although we still cannot confirm whether the red color is intrinsic, we do find that the “blue color” criterion can filter out normal TDEs whose optical–UV spectral energy distributions (SEDs) are either severely contaminated by prominent emission lines (especially H α ) or heavily dust-reddened. Hence, its potential selection effect may have been imprinted on the whole optical TDE family. Blackbody fitting on the optical (rest-frame ∼4000–7000 Å) and optical–UV (∼2000–7000 Å) SEDs of four TDEs with high-cadence UV observations shows that T _bb rises by ∼40%−110% when the UV bands are included. The power-law models ( f _λ ∝ λ ^− ^α with α = 2–3) can fit the rest-frame ∼2000–7000 Å SEDs more consistently, indicating that SEDs should peak at shorter wavelengths, than simple blackbodies. Hence, the estimated released energy for the optical–UV-bright but X-ray-faint TDEs based on blackbody SED fitting should be significantly lower than the intrinsic energy.